Ensuring health equity during the COVID-19 pandemic: the role of public health infrastructure - Georges C. Benjamin (Pan American Health Organization, 2020)
The COVID-19 pandemic has significantly stressed public health systems around the world and exposed the gaps in health care for underserved and vulnerable populations. In the context of the social determinants of health, focusing on health system preparedness is paramount for protecting the health of all of society. Faced with old threats (e.g., re-emergence of measles), disruptive new technologies (e.g., electronic cigarettes), increased challenges (e.g. drug-resistant organisms), and new threats (e.g., the current pandemic, climate change, politicized misinformation), our health systems must be robust and resilient. The response must include those who now suffer disproportionately-the poor and the vulnerable. Current World Health Organization priorities call for infrastructures capable of detecting, monitoring, and responding to health emergencies, such as COVID-19, and the health impacts of climate change in the context of health for all. Health care infrastructure can be better prepared and more equitable if systems are strengthened by building on core competencies and following the recommendations made for leadership, stakeholder involvement, accreditation, data collection, and funding resources. Ensuring health equity in a pandemic requires robust and resilient public health infrastructure during normal times.